Teaching second-grade students to write sequential text. Issue 6 (2nd November 2018) - Clark, Sarah K.; Neal, John
ABSTRACT: With the adoption of the English Language Arts Common Core State Standards, writing has become an increasingly important area of instruction. Moreover, there has been an increased sophistication in the types of writing required of young children and the use of textual evidence expected in student writing. Historically, children have not been routinely taught explicit strategies for writing, but have been exposed to less rigid writing instruction such as Writer's Workshop. The current study examined an explicit writing strategy, the Read-to-Write Strategy, to determine its effectiveness in teaching young children how to write sequential text. A single subject design (N = 40) was used to compare the writing of second graders before and after instruction. Results indicated that the Read-to-Write Strategy significantly increased the quality of sequential text from the pre- to post-instruction with a large effect size reported. Implications and recommendations for educators and researchers are provided.